1998
DOI: 10.1007/s002470050506
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence due to an infrasphincteric ectopic ureter: why the delay in diagnosis and what the radiologist can do about it

Abstract: The classic history of constant urinary dribbling in a successfully toilet-trained girl should immediately lead to an imaging search for the portion of kidney (or entire kidney) drained by an infrasphincteric ectopic ureter. EU should usually be the first imaging performed and is often the only imaging study needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…), and are especially difficult to find if they are draining a hypofunctioning kidney due to lack of positive imaging findings. 5 Because of this, diagnoses are at times unfortunately made later in life, with case reports of women being diagnosed as late as 70 years of age. 1 Studies have shown a mean delay in definitive diagnosis as anywhere from 2 to 5 years after initial presentation.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…), and are especially difficult to find if they are draining a hypofunctioning kidney due to lack of positive imaging findings. 5 Because of this, diagnoses are at times unfortunately made later in life, with case reports of women being diagnosed as late as 70 years of age. 1 Studies have shown a mean delay in definitive diagnosis as anywhere from 2 to 5 years after initial presentation.…”
Section: 3mentioning
confidence: 99%
“…1 Studies have shown a mean delay in definitive diagnosis as anywhere from 2 to 5 years after initial presentation. 1,5 This indicates that there must be a high index of suspicion for ectopic ureter in a girl or woman presenting with unrelenting urinary incontinence regardless of age. 1,3,4,5 This case details a 17-year-old adolescent female with an ectopic ureter diagnosed late in life.…”
Section: 3mentioning
confidence: 99%
“…In men, the extravesical ectopic orifice is always suprasphincterically and the ectopic orifice sites may be in bladder neck, seminal vesicle, vas deferens, prostate or epididymis [7]. Normal urination together with continuous incontinence are patognomic features for infrasphincteric ureteral openings [8]. Ectopic ureteral insertion is most commonly associated with complete duplication and obstruction [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 When the upper pole moieties are small or dysplastic, diagnosis can be subtle and the condition can go unrecognized by routine methods. 2 Successful confirmation of the ecotopic ureter openings preoperatively also remains a diagnostic challenge. We report a rare case in which, although conventional imaging demonstrated bilateral duplicated renal collecting systems, it failed to depict the exact site of insertion of the right ectopic ureter.…”
Section: Introductionmentioning
confidence: 99%